Patients' experience of suffering a distal radius fracture with long-lasting impairment-a qualitative study. - Hanna Südow; Cecilia Mellstrand Navarro; Sari Ponzer; Caroline Olsson (PLoS ONE)
Background Every year a large number of people suffer a distal radius fracture and some of them never regain their activity level. The correlation between radiographic features and outcome explains some but not all the disability perceived after fracture healing and rehabilitation. Little is known of the persons reporting persistent upper limb dysfunction. The aim of this study was to improve the understanding of the experience of persistent impairment, treatment, and recovery process after a distal radius fracture, with a focus on patients with benign radiographic and injury features but without full restoration of function. Materials and methods This is a qualitative study performed through semi structured interviews analyzed with content analysis. The participants had previously been treated at Södersjukhuset hospital, Stockholm, Sweden for a distal radius fracture and reported that they had not regained their previous function. The sampling was purposeful and participants who were assumed to carry a lot of information were selected to participate. All 17 interviews were recorded, transcribed, and coded. Codes were grouped and categories formed. Results Three main categories were inductively identified from the data. 1. Limitations in life due to persistent impairment-the description of what was not regained, physically, mentally, and activity-wise. 2. Being a patient-the participants' description of experiences and feelings when assuming the role as a patient. 3. The last main category identified was personal circumstances such as having to care for children, being alone or having a partner, having a demanding employer or the person's inherent personality and attitude. Conclusion Patients suffer from impairment difficult to measure after a distal radius fracture. During the treatment and recovery process their experience as being patients, their perceived level of knowledge and their personal circumstances all play important roles in understanding how the participants experienced their recovery.